(untitled) (VETERINARIA, 2020)
The efficacy of Diatomaceous earth (DAE) in reducing the detrimental effects of aflatoxin (AF) in broiler diet was evaluated. DAE was supplemented 2000 mg/kg of feed along with 0.5 and 1 ppm of AF in feed. A total of 240 healthy day old broiler chicks were divided into 6 groups comprising of control and treatment groups. Feeding of AF resulted in reduction in size of the thymus, spleen and bursa of Fabricius. In addition, petechial haemorrhages were observed on the surface of the thymus. Histopathology revealed varying degree of lymphocytolysis and depletion of lymphoid cells in thymus, spleen and bursa of Fabricius. In addition, the ceacal tonsils also revealed a mild to moderate degree of lymphoid depletion. The supplementation of DAE to aflatoxin-mixed feed revealed significant improvement characterised by decreased severity of lesions in lymphoid organs. The macroscopic and microscopic changes in the birds fed DAE in combination with AF included those that were observed in AF- alone fed birds, but of reduced magnitude and severity. The study concluded that 2% DAE in feed can be effectively used to reduce the the histotoxic effects of aflatoxin on lymphoid organs in broiler chicken.